Factors associated with abandonment of alcohol and other drugs treatment in street residents (Research, Society and Development, 2021)
The study aimed to evaluate the factors associated with the abandonment of alcohol and other drug treatment among homeless people in Porto Velho/RO. For the realization, we opted for a descriptive investigative field research supported by a qualitative approach. The research was carried out together with the Street Clinic (ECR) team in their services, with 12 homeless people according to the inclusion and exclusion criteria, using the interview technique with a semi-structured script, considering the ethical and legal aspects of the research determined by Resolution 466/12 of the National Health Council / Ministry of Health. The data were transcribed in full for analysis, respecting the confidentiality of the information. Through the speeches and in view of the empirical observation of the reports, three thematic categories were selected, namely: Experienced Feelings and the Right to Citizenship, Gaps in the Family Context and the Use of Alcohol and Other Drugs, and Addiction and Damage to Treatment Abandonment. The importance of the RCT as a facilitator in the access of this population to health services was observed. The low investment by public policies in the program was also evidenced, which highlights the need for improvements and adequate investment, as this is directly linked to the health services offered to homeless people.